Radical scavenging potential, antiinflammatory and antiarthritic activity of isolated isomer Methyl-γ-Orsellinate and roccellatol from Roccella montagnei Bel - Syed Zameer Ahmed Khader; Sidhra Syed Zameer Ahmed; Thangakumar Arunachalam; Sanjeeva Nayaka; Senthil Kumar Balasubramanian; Syed Tajudeen SyedAmeen; Ponmurugan Ponnusamy (Faculty of Pharmacy, Cairo University, 2018)
The burden of multiple drug resistance towards chronic diseases is rapidly increasing globally at an alarm rate. The present study aims to isolate active principles via bioassay guided fractionation of traditionally used lichen Roccella montagnei for in vitro radical scavenging activity with potential to combat arthritis and inflammation. The results of proximate composition and mineral analysis revealed the presence of essential amount of micro and macro nutrients which are required for secondary metabolite production. Fractions of Roccella montagnei and pure compounds were assessed for its in vitro antioxidant (DPPH, FRAP, OH radical, SOD, CAT, GPX), antiarthritic and antiinflammatory activity. The results indicates that lichen sample and fractions exhibited potent radical scavenger demonstrated in vitro antiarthritic and antiinflammatory activity in dose dependent manner. Bioassay fractionation lead to isolation of two pure compounds ie., Compound I and Compound II which were characterized using spectral data such as FT-IR, 1H NMR, 13C NMR, DEPT NMR spectroscopy, COSY & HMQC NMR spectroscopy and LC-MS analysis and was identified as Methyl-γ-Orsellinate (C9H10O4) a novel isomer from fractions E2d5a with a molecular weight of 182.2 and Roccellatol (C12H16O7) from fractions D3d4c with a molecular weight of 272.3. The present findings suggest that the secondary metabolites present in the lichens have direct relation, with biological activities revealing different properties and can be a future novel antioxidant and a potent anti-arthritic agent.